ADHD patients with DIRAS2 risk allele need more thalamic activation during emotional face-voice recognition. (February 2022) - Hillmann, Bastian; Zuberer, Agnieszka; Obermeyer, Lena; Erb, Michael; Scheffler, Klaus; Nieratschker, Vanessa; Ethofer, Thomas
Highlights: During emotion recognition thalamus activation differs considering DIRAS2 status DIRAS2 risk allele in ADHD patients is associated with higher thalamus activation Differences could be due to compensatory mechanisms in neural networks